Competitiveness of Egyptian potatoes exports in the most important world markets - Shehata, Gaber Ahmed Bassyouni; Elgabery, Amal A.; Alskran, Ali K. A. (Advances in Social Sciences Research Journal, 2020)
The competitiveness of exports of potatoes was measured by calculating some of the competitiveness indicators including market share index, market penetration rate, price ratio index, virtual comparative advantage index, geographical concentration index (Gini Hirschman) and the index of instability. The measurement of the external demand function on the quantity of Egyptian exports of potatoes in the world markets depends on the total domestic production of potatoes. It was also found that this variable explain about 39.7% of the changes in the quantity of Egyptian potato exports to the world markets. A study of the forecast results of the selected models until 2024 shows that the value of agricultural exports of potatoes crop is expected to reach about $ 277.7 million in 2024, with an increase of about 77.4% compared to 2018. The research, based on its findings, reached some recommendations that could benefit the Egyptian economic policy makers in this field.